2020
DOI: 10.14738/assrj.612.7547
|View full text |Cite
|
Sign up to set email alerts
|

Which factors most challenged instructors’ integration of technology in KSA education between 2009 and 2019? A systematic analysis review

Abstract: The introduction of technologies such as E-learning, Learning Management System (LMS), Twitter, Facebook etc. into teaching and learning practices can make the education environment more attractive and active. However, there are some impediments, both external and internal, that influence the use of this technology. As a result, this study attempts to review and analyse studies that have investigated the important internal and external obstacles to faculty members’ use of technology in Saudi education. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…H3 is accepted by the results of this study, which further clearly show that training has a positive influence on the acceptance of the technology, and this corresponds with research conducted by Almaiah et al (2022, Alharbi et al (2019), and Alshehri and Alahmari (2021).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…H3 is accepted by the results of this study, which further clearly show that training has a positive influence on the acceptance of the technology, and this corresponds with research conducted by Almaiah et al (2022, Alharbi et al (2019), and Alshehri and Alahmari (2021).…”
Section: Discussionsupporting
confidence: 87%
“…Based on 16 studies conducted between 2019 and 2022 in the field of intention and acceptance of the use of technology in the field of education in the context of Saudi Arabia which mentioned 33 factors affecting the acceptance as well as the actual intent to be used advanced technologies, which are the study of Khan et al (2021, Almaiah et al (2022), Afandi (2022), Alharbi et al (2021), Chatti andHadoussa (2021), Al-Ghurbani et al (2022), Alsmadi (2020), Alharbi et al (2019), Alammary et al (2021), Al-Shargabi et al (2021, Alshehri and Alahmari (2021), Binyamin et al (2019), Badwelan and Bahaddad (2021), and Alkhaldi et al (2021).…”
Section: Conceptual Model and Hypotheses Developmentmentioning
confidence: 99%
“…[90] 2019 A study by Ibrahim, Mohamed, Aldhafeeri and Alqdah [90] indicated that a lack of motivation, time and training were the essential factors that prevented educators' use of the Blackboard system at the university. Training, Time as policy, equipment, technical issues, administrative support, attitude to towards changes, knowledge, skills, interests, motivations, pedagogical issues, English skills, workload, inancial issues, IT resources [33] 2019…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The study by Alharbi [33] indicate a lack of training and a lack of time were the major factors that delayed the use of Technology by educators in Saudi institutions, and other factors assisted a negative effect in technology educators in Saudi institutions as policy, equipment, technical issues, administrative support, attitude to towards changes, knowledge, skills, interests, motivations, pedagogical issues, English skills, workload, inancial issues, IT resources. Content quality system navigation, ease of access, system interactivity, instructional assessment system learnability learning support instructional assessment ease of use [34] 2019 the results revealed that perceived ease of use is affected by six factors (content quality, system navigation, ease of access, system interactivity, instructional assessment and system learnability).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation